Engaging fans and the community in social media: interaction with institutions of higher education on Facebook. Issue 1 (2nd January 2017) - Brech, Felicitas M.; Messer, Uwe; Vander Schee, Brian A.; Rauschnabel, Philipp A.; Ivens, Bjoern S.
ABSTRACT: Although many universities use social media to interact with stakeholders, little is known about the underlying mechanisms. Drawing on theories of self-presentation and community engagement, we develop a theoretical model to explain these crucial outcome factors. We then test the model based on secondary data from 159 universities. Our findings reveal the double-edged nature of community size: universities with a strong reputation tend to have more Facebook fans, but having many Facebook fans has detrimental effects on individual fan engagement. Furthermore, the frequency of updates is a crucial factor, as too frequent and too infrequent updates lead to lower levels of fan engagement. We discuss theoretical implications for online communities and derive implications for social media managers.